2022
DOI: 10.3390/businesses2010007
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Investigation on Bubbles Contagion in Scandinavian Real Estate Markets

Abstract: This paper investigates the presence of speculative bubbles in the Scandinavian countries namely Denmark, Finland, Norway, and Sweden over the period from 1980Q1 to 2018Q4 and searches for evidence of bubble migration among those countries. First, we apply the GSADF test developed by Phillips et al. (2015) on quarterly housing price-to-rent ratios to test for exuberance and episodic bubbles. Subsequently, we examine bubble migration between these markets using the non-parametric model with time-varying coeffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…Broadly consistent with recent empirical research studies [9,26], the findings arising from this investigation provide important theoretical and market insights into the distinct short-run and long-run dynamics between macroeconomic factors and the pricing structures across the various property market segments. Importantly, the results highlighted market compartmentalisation issues, and, more precisely and appositely, were in agreement with the well-stablished submarket hypotheses in the literature with each sample housing submarket governed by both common and unique macroeconomic forces at play within the wider housing market and the economic environment.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Broadly consistent with recent empirical research studies [9,26], the findings arising from this investigation provide important theoretical and market insights into the distinct short-run and long-run dynamics between macroeconomic factors and the pricing structures across the various property market segments. Importantly, the results highlighted market compartmentalisation issues, and, more precisely and appositely, were in agreement with the well-stablished submarket hypotheses in the literature with each sample housing submarket governed by both common and unique macroeconomic forces at play within the wider housing market and the economic environment.…”
Section: Discussionsupporting
confidence: 82%
“…For instance, Borgersen [11] empirically confirmed the linkage between the PtR and the loan to value ratio with the return on leverage, partially determined by the interrelationship between real estate price growth and borrowing cost. In a more recent study, Bago et al [26], using the GSADF test, empirically observed spatial diffusion of housing bubbles price-to-rent bubbles between Denmark, Finland, Norway and Sweden, with the degree of contagion strengthened by their geographical proximity. With regard to the Chinese housing market, Wu and Jiang [27], in a comparative study, evaluated the price-to-rent ratios and the price-to-income ratios of a number of regional housing markets.…”
Section: Literature Reviewmentioning
confidence: 99%